Prevalence of neuropathic component of pain in a cohort of patients admitted to an Internal Medicine Department for chronic pain - Giuseppe Chesi; Giovanni Scanelli; Fabio Gilioli; Erio Scalabrini; Claudio Giumelli; Francesca Franco (Italian Journal of Medicine, 2015)
Due to the increasing age of the population the number of people suffering from chronic pain has significantly increased. People with chronic pain suffer from various diseases. Often this pain is not adequately controlled and is refractory, while its neuropathic component, which requires a different treatment, is perhaps underestimated compared to more properly nociceptive pain. The purpose of this study was to evaluate the presence of a neuropathic component in a cohort of 105 patients consecutively admitted to three Internal Medicine Units in Emilia Romagna. For the identification of the component of neuropathic pain diagnostic (DN4) questionnaire, previously validated, has been used. The average age of the patients studied was 64.4 years. The group of subjects with chronic non-cancer pain (78%) was numerically higher than the group of patients suffering from cancer pain (22%). All patients had pain and, according to the visual analogue scale (VAS), pain ranged from moderate to severe (median 7). Although without reaching statistically significant data, according to the VAS scale, cancer pain had an average higher value than non-cancer pain (7 vs 6.5). The prevalence of neuropathic component of pain was higher in patients with non-cancer pain (66% vs 57%). Instead, the recorded pain intensity in patients with neuropathic component was statistically much higher than the group in which the neuropathic component was absent (6.9 vs 6.1; P<0.05). In patients suffering from chronic pain, regardless of its nature and its etiology, the presence of a neuropathic component is significant. We must become aware of it and must search for it regularly through appropriate tools, such as the DN4 questionnaire. The presence of a neuropathic component usually makes the pain more intense and more refractory to treatments commonly used. Search for it may have therapeutic implications, suggesting that doctors use drugs active on this component. Since the majority of patients suffering from chronic pain are admitted to internal medicine wards, this awareness ought to become cultural heritage for the internist.